Hough's cardiorespiratory care :an evidence -based, problem-solving approach - Hough, Alexandra (London Elsevier, 2018)
The latest edition of this must-have text book promises an evidence-based and practical approach covering the very latest in cardiorespiratory care. The textbook covers a wide range of cardiorespiratory conditions and discusses treatment of patients in different clinical settings such as critical care, the ward area and out-patient departments. It begins with physiology and pathology and progresses into a detailed patient assessment section and a discussion of specific respiratory and cardiac conditions. The final section covers different groups of people who may require physiotherapy such as infants, children, and adults with specific conditions including a considered section on palliative care. Critical thinking is facilitated by clinical reasoning boxes in the text, and problem-solving is aided by case studies at the end of each chapter. There are also relevant practice tips to enable transfer of learning into the clinical environment. The text is supported by over 280 line drawings and diagrams along with over 70 x-rays and photographs to further illustrate the points under discussion.--
Note continued: 22.Modifications for different disorders -- pt. VI Does it work? -- 23.Evaluation of cardiorespiratory physiotherapy.
Preceded by Physiotherapy in respiratory and cardiac care / Alexandra Hough. 4th ed. 2014.
Keywords: Respiratory organs; Heart; Respiration Disorders; Physical Therapy Modalities; Respiratory organs